Tracer Study of Outstanding Athletes - Irpani; Albadi Sinulingga; Suryadi Damanik; Rafika Ardilla (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to trace the achievements of athletes from several sports. This study used a descriptive qualitative method. Data collection techniques using observation, questionnaires, and documentation. In this study, the subjects of the study were athletes who were still actively training. The results showed that the social agent aspect had an impact on athlete achievement, namely: parents (74%) in the good category, coaches (81%) in the good category, teachers (78%) in the good category, peers (74%) in the good category. good environment (87%) in very good category, mass media (78%) in good category, and the correlation between social agent and achievement is 80% in good category. Based on the research results, each of these social agents has a role in achievement. High or low athlete achievement is not only the social agent aspect that influences it. Achievement was created from many factors that influence it.